2013
DOI: 10.3748/wjg.v19.i26.4214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amitriptyline on gastrointestinal function and brain-gut peptides: A double-blind trial

Abstract: Low-dose AMT could slow OCTT, make the stomach less sensitive and increase the plasma levels of ghrelin and NPY. Thus, we recommend the use of low-dose AMT for functional gastrointestinal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…The literature supports this hypothesis. Huang et al [26] demonstrated that at least in healthy volunteers, low dose of amitriptyline make the stomach less sensitive and increase the plasma levels of ghrelin. However, more studies are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The literature supports this hypothesis. Huang et al [26] demonstrated that at least in healthy volunteers, low dose of amitriptyline make the stomach less sensitive and increase the plasma levels of ghrelin. However, more studies are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that low-dose AMT is well tolerated and can significantly improve patient symptoms, sleep, and quality of life. Low-dose AMT may be an effective treatment for globus pharyngeus [4. A previous study suggested that AMT could modify brain-gut axis function, upregulating brain-gut peptides, reducing the visceral sensitivity, and regulating the secretory and motor functions of the GI tract [4]; thus, the GI symptoms and emotional well-being could be significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose AMT may be an effective treatment for globus pharyngeus [4. A previous study suggested that AMT could modify brain-gut axis function, upregulating brain-gut peptides, reducing the visceral sensitivity, and regulating the secretory and motor functions of the GI tract [4]; thus, the GI symptoms and emotional well-being could be significantly improved. In the present study, we observed that PAR therapy is more efficacious than empirical high-dose antacid treatment or even the low-dose AMT therapy in alleviating globus symptoms and producing global improvements for refractory globus patients [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations